Specificity of the functioning of the Supreme Anticorruption Court in Ukraine: international experience and Ukrainian realities - Prokopiv, Bohdan (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
In this article, author  analyzes the international experience of the creation and functioning of anti-corruption courts,  the provisions of the Law of Ukraine «About the Highest Anticorruption Court» and advantages and disadvantages of creating anticorruption courts in Ukraine.